Contributors to and consequences of burnout among clinical genetic counselors in the United States. Issue 1 (28th July 2021) - Caleshu, Colleen; Kim, Helen; Silver, Julia; Austin, Jehannine; Tibben, Aad; Campion, MaryAnn
Abstract: Prior research has found that many genetic counselors (GCs) experience burnout. Studies of other clinicians have demonstrated that burnout can have significant detrimental consequences for clinicians, patients, and the healthcare system. We sought to explore the prevalence of, contributors to, and consequences of burnout among GCs. We performed a secondary data analysis of baseline data from Me‐GC, a randomized controlled trial of meditation for GCs. We applied a systems model of burnout proposed by the National Academy of Medicine (NAM), which depicts burnout arising from a combination of contributors that include both work system and individual mediating factors, and then leading to consequences. Validated self‐report scales were used to measure burnout and most contributors and consequences. Female and white GCs were over‐represented in our sample. Over half (57.2%) of the 397 participants had Professional Fulfillment Index scores indicative of burnout. Multiple potential contributors were associated with burnout, consistent with its known multifactorial nature. Among work system factors, higher levels of burnout were associated with insufficient administrative support, lack of autonomy, and not feeling valued by non‐GC colleagues. Individual mediating factors associated with greater burnout included higher levels of anxiety, depression, and stress. Participants with lower levels of burnout reported greater mindfulness, resilience, and use of professional self‐care behaviors. Among variables categorized as consequences, higher levels of burnout were associated with lower levels of empathy, counseling alliance, and positive unconditional regard, as well as higher reactive distress, and a greater desire to reduce the amount of time spent on clinical care. Given the prevalence and potential consequences of burnout observed here, it is imperative that the field take steps to mitigate burnout risk.